Plum Pox Virus in Japanese Plum from Argentina: Serological Detection and Molecular Characterization of an Isolate from cv. Red Beauty - Dal Zotto, Angélica (2014)
APlum pox virus(PPV) isolate detected in a Japanese plum orchard in Poci-to (San Juan, Argentina) was transmitted mechanically toPrunus tomento-saandNicotiana benthamiana. DAS-ELISA and DASI-ELISA indicated thevirus presence and serological relationship with D-strain isolates; IC-RT-PCR amplified a 1.2-kb fragment of the virus genome encoding theCP-3′nc region. The analysis of the sequence showed the presence of theDAG motif at the 5′end of the capsid protein and the Rsa I and Alu I sitesat the 3′end. The phylogenetic relationships and multiple alignment withPPV isolates from NCBI database indicated greatest (+98%) homologywith the D strain and close identity with MNAT1 (\AF360579) USA peachisolate. The sequence analysed showed two amino acid mutations towardsthe 5′N-terminus of CP (the most variable region) with respect to a con-sensus of PPV D-strain isolates. This is the first molecular characterizationof 3′terminal genome region of PPV isolate to confirm D strain in a Japa-nese plum from Argentina